Review of deterministic networking technology - Xiaodong DUAN; Peng LIU; Lu LU; Tao SUN; Zhiqiang LI (Dianxin kexue)
Deterministic networking was proposed to meet the demands of high bandwidth, low delay and high reliability for audio and video, industrial control, power protection and other applications.With the development of new services such as virtual/augmented reality and cloud games, the application scenarios of deterministic networking have been enriched, and the scope of deterministic networking technology has also been extended.In view of the overall consideration of current application scenarios, technical standards and industrial development, the strong and weak deterministic requirements and characteristics for different scenarios were analyzed, as well as different kinds of deterministic networking technologies, including scientific and engineering.The diversified development path of deterministic networking was proposed and the development of combination technologies of deterministic networking for 6G and computing force network was looked forward.